The effect of hopelessness on violence tendency: Turkish football fans - Yalcin Ilimdar; Ekinci Nurullah Emir; Ayhan Cihan (Sciendo, 2021)
This study aimed to analyze the relationship between the hopelessness and violence tendency of football fans and to investigate the differences between these variables and various demographic variables. The research group was formed by 398 male volunteer football fans who watched the Elazigspor (Sports Toto 1st League ) matches in the 2018-2019 season in Turkey. In addition to demographic variables in the study, the Violent Trend Scale and Beck Hopelessness Scale were used. The SPSS program was used to analyze the data. Independent sample t-test, one-way ANOVA, pearson correlation, and linear regression analysis were used in the analysis of the data. In the findings of the research, it was determined that there was a moderate positive relationship between the variable of hopelessness and the tendency toward violence. It was determined that there was a statistically significant difference in the tendency toward violence according to the variables of fans going to away games, the duration of watching matches at the stadium, and with whom fans watched the matches. As a result, as the level of fans' hopelessness increased, it was observed that there was an increase in violent tendencies. In addition, those who went to watch away matches, those who watched matches at the stadium for a long period of time, and those who went to watch matches with friends were found to have high levels of violent tendencies.